2003
DOI: 10.1016/j.vetmic.2003.08.010
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cytokine response to experimental feline infectious peritonitis virus infection

Abstract: Feline infectious peritonitis virus (FIPV) is a coronavirus that causes sporadic fatal disease in cats characterized by vasculitis, granulomatous inflammation and effusive pleuritis/peritonitis. Histologic changes in lymphoid tissues include lymphoid hyperplasia, lymphoid depletion, histiocytosis, and granuloma formation. Although viremia occurs, histologic lesions are not found uniformly throughout lymphoid tissues. We used experimental infection of cats with a highly pathogenic FIPV isolate, UCD8, to study h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 34 publications
5
75
1
2
Order By: Relevance
“…In contrast, the 18 cats that died within 4 weeks of infection demonstrated a precipitous drop in blood lymphocytes starting at 2 weeks post-infection. A similarly profound decrease in blood lymphocytes has been previously associated with disease signs in experimental FIPV infection (Dean et al, 2003), and varying degrees of lymphopenia are a common feature of naturally occurring FIP (Pedersen, 2009). Although T lymphocytes were entering diseased tissues, their proportion was low compared to macrophages and their numbers not appear sufficient to be solely responsible for the pronounced lymphopenia.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In contrast, the 18 cats that died within 4 weeks of infection demonstrated a precipitous drop in blood lymphocytes starting at 2 weeks post-infection. A similarly profound decrease in blood lymphocytes has been previously associated with disease signs in experimental FIPV infection (Dean et al, 2003), and varying degrees of lymphopenia are a common feature of naturally occurring FIP (Pedersen, 2009). Although T lymphocytes were entering diseased tissues, their proportion was low compared to macrophages and their numbers not appear sufficient to be solely responsible for the pronounced lymphopenia.…”
Section: Discussionmentioning
confidence: 67%
“…FIPV does not appear to replicate in enterocytes (Chang et al, 2010;Pedersen et al, 2012), and was first associated with macrophages by electron microscopy and immunohistochemistry (Ward, 1970;Pedersen and Boyle, 1980). Dean et al (2003) studied the distribution of FIPV by immunofluorescence at the time of death in experimentally infected cats and also found macrophages to be heavily infected in mediastinal and mesenteric lymph nodes and spleen, with much less evidence of infection in peripheral tissues such as popliteal and cervical lymph nodes and bone marrow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesized that virulent FCoV strains arise by a genomic mutation, possibly within the 3c gene (Pedersen, 2009;Pedersen et al, 2009;Chang et al, 2010), but the mutation potentially involved in this pathogenic shift has never been identified (Kennedy et al, 2001;Rottier et al, 2005;Dye and Siddell, 2007;Lin et al, 2009). Experimental studies reported a low morbidity rate in cats inoculated with ''virulent'' FCoVs formerly classified as FIPV (Pedersen, 1987;Kipar et al, 2001;Dean et al, 2003;Kiss et al, 2004). All these findings support the hypothesis that the development of FIP depends on a specific FCoVhost interaction, mostly based on cell-mediated immunity (Pedersen, 1987(Pedersen, , 2009.…”
Section: Discussionmentioning
confidence: 78%
“…Specifically, although biased by the low number of observations and by the high individual variability, these results suggest that some sequences of FCoV protein N from ''avirulent'' or ''mixed'' strains can stimulate cell-mediated immunity, especially in cats in which cell-mediated immunity is primed by chronic diseases. Future larger studies are required to confirm the possible role of FCoV itself in stimulating the production of IFN-g, the key cytokine of cell-mediated immunity involved in the response against FCoVs and consequently responsible of viral persistence (Gunn-Moore et al, 1998;Dean et al, 2003;Foley et al, 2003;Kiss et al, 2004;Berg et al, 2005;Gelain et al, 2006;Giordano and Paltrinieri, 2009).…”
Section: Resultsmentioning
confidence: 99%